Advising Based on Self-Experimentation Assignments Increases the Magnitude of Weight Loss - Lee, Mindy (Curr Dev Nutr, 2020)
OBJECTIVES: Individualized Diet Improvement Program (iDip) has been developed for a sustainable diet for weight management through self-experimentation with emphasis on increasing protein and fiber and reducing caloric intake. Upon a successful feasibility test with the first study completed in 2018 (iDip 1), we hypothesized that assigning homework and advising based on response would improve weight loss along with the dietary changes. METHODS: Thirty adults (BMI >25 kg/m(2)) were enrolled in a 2-year study (iDip 2). The study comprised of 22 dietary sessions over 12 months, identical to iDip 1. Participants were assigned to complete a self-experimentation homework after each session and received advising based on responses. As visual feedback, weekly weight charts and dietary analyses in the form of Protein-Fiber (PF) plot were offered. Daily weights, body composition, waist circumference were collected and 24-hour dietary records were obtained. RESULTS: Six participants dropped out, leaving 24 participants (80%). Mean body weight change (n = 24) in iDip 2 at 8 months was −6.2 ± 1.5% while mean body weight change (n = 12) in iDip 1 was −5.2 ± 1.1%. Nine out of 24 participants (38%) achieved clinically meaningful weight loss (>5% of initial body weight) with a mean body weight change of −12.9% ± 2.8. The magnitude of weight loss of the successful group in iDip 2 was significantly greater (P < 0.05) than that of the successful group in iDip 1 where 5 out of 12 participants (42%) achieved >5% weight loss (mean body weight change: −8.9 ± 1.3%). Skeletal muscle mass was well-maintained with a mean change (n = 18) of −0.7 ± 0.2% at 6 months. Waist circumference (n = 18) was significantly decreased (P < 0.05) from baseline by −6.5 ± 1.3 cm. 24-hr records showed improvements in protein and fiber intake throughout the study. Although no significant differences were found in protein and fiber intake between two studies, higher mean protein and fiber intake were observed at 6 months in iDip 2. CONCLUSIONS: Self-experimentation assignments followed by individualized feedback significantly increased the magnitude of weight loss over the previous study with protein intake to maintain skeletal muscle mass as evidenced by its minimal loss. The success rate of participants achieving >5% weight loss did not improve in this study. FUNDING SOURCES: USDA NIFA ILLU-698–908; NIBIB NIH (CA).